ETIKA DALAM PERPAJAKAN PENERAPAN ETIKA PROFESI AKUNTAN DALAM PRAKTIK PERPAJAKAN DI INDONESIA - Muslimah, Hamidah (Journal Of Accounting And Finance, 2026)
Taxation is a crucial instrument in supporting national development, thus accountants have a strategic role in ensuring compliance and transparency in reporting. In practice, accountants often face ethical dilemmas when companies attempt to minimize their tax burden through illicit means. Therefore, the application of accounting professional ethics is crucial for ensuring tax reporting is conducted with integrity and social responsibility. This article uses a qualitative descriptive approach through a literature review that summarizes the application of accounting professional ethics in tax practice in Indonesia. The study results indicate that adherence to the professional code of ethics can prevent tax report manipulation, increase taxpayer compliance, and strengthen fiscal governance. Furthermore, the application of ethics also contributes to the reputation of the accounting profession and builds trust between companies, tax authorities, and the public. Therefore, accounting professional ethics in taxation is not merely a normative rule, but a crucial foundation for the sustainability of the national fiscal system and the role of accountants as guardians of integrity in tax practice.